Innovation in Pancasila Education Learning: The Role of Interactive Multimedia in Enhancing Students' Learning Interest - Eka Dayani Yulianti; Desi Fitri Utami; Brian Rusty Santosa; Deni Zein Tarsidi (CAKRAWALA: Journal of Citizenship Teaching and Learning, 2025)
The education of Pancasila in elementary schools is crucial for developing students’ character and fostering a sense of national identity. Nevertheless, traditional teaching approaches frequently fail to engage students, leading to diminished participation and comprehension. This research aims to examine how interactive multimedia can enhance students' interest in learning Pancasila Education at the elementary school level. The investigation was carried out using a qualitative case study approach at an elementary school located in the Banjarsari District of Surakarta City. To gather data, techniques such as observation, interviews, and literature reviews were employed to assess the implementation and effectiveness of interactive multimedia in the educational process. The findings indicated that interactive multimedia tools, including animated videos, educational games, and digital comics, can substantially boost students' interest, engagement, and understanding in studying Pancasila Education. These interactive tools enable students to visualize abstract ideas, actively participate in their learning, and connect the content to their daily lives. However, the research also highlighted several constraints, including differences in multimedia quality, technological limitations, and the requirement for extensive resources for effective implementation. Engaging multimedia that facilitates direct interaction among students has proven to be more effective compared to passive formats like videos. The study concluded that interactive multimedia is essential in making the learning of Pancasila Education more vibrant, participative, and meaningful. It is advised that educators and policymakers advocate for the incorporation of interactive multimedia by providing teacher training, enhancing technology infrastructure, and fostering collaboration in developing high-quality educational materials.